TERCER CASO DE VASCULITIS LEUCOCITOCLÁSTICA CUTÁNEA SECUNDARIA AL USO DE OXACILINA: REPORTE DE CASO - Daniel Martin Arsanios (Asociación Colombiana de Infectología, 2021)
Leukocytoclastic vasculitis is a pathology that involves small vessels and whose cause has been predominantly described as idiopathic. The clinical case of a 78-year-old woman with hypertension, diabetic and chronic stage 5 kidney disease, who presented limited skin lesions after administration of oxacillin for management of bacteremia by MSSA. The clinical presentation consisted on palpable purpura predominantly in the lower limbs and painful coalescent lesions that formed blisters of hemorrhagic content. Lesions gradually resolved after the change of the therapy mentioned above. The biopsy was compatible with leukocytocastic vasculitis, with paraclinics who ruled out infectious and autoimmune causes.